Decline to fall - Wass, Douglas (Oxford University Press, 2008)
This book provides the first comprehensive and authoritative account of the events leading up to the UK seeking a massive loan from the IMF in 1976 which almost precipitated a financial crisis on a par with those of the 1930's and early post War period. Sir Douglas Wass, who was permanent Secretary to the Treasury at the time, provides a unique first hand account of the events that took place as the crisis unfolded and the decision-making process...